Penerapan Metode CIBEST Berbasis Indeks dan Kuadran dalam Memberdayakan Masyarakat di Lambaga Zakat Kota Malang - Basar Dikuraisyin; Faby Toriqirrama; Muhammad Asrori Ma’sum (Management of Zakat and Waqf Journal (MAZAWA), 2022)
this study describes a strategy for community empowerment through the CIBEST approach which is oriented towards target identification, mapping and program determination. This study provides a solution to the problem of inaccuracy in the mustahik empowerment program by zakat institutions. This research is a qualitative type of field applied research with a descriptive approach. Collecting data using the triangulation method, interviews with zakat institutions in the Malang City area, namely the National Amil Zakat Agency (BAZNAS) Malang City, Lazizmu Malang City. Observations were made on the mustahik community (social community) by looking at the before and after aspects. The results of the study found several things, 1) The application of the CIBEST method was carried out in three stages. First, identifying mustahik’s through a submission and recommendation system, feasibility survey and deliberation to determine and map mustahik’s needs. Second, mapping the empowerment program. Zakat institutions map the status of mustahik's empowerment in the form of four quadrants (quadrants I-IV) in the form of material and spiritual categorization. Third, determining the program. 2) The impact of implementing the CIBEST Model is; a) before applying the CIBEST quadrant in the aspect of quadrant I (prosperity) it changed from 11 families to 42 families; b) in quadrant II (material poor) originally 36 families changed to 18 families; c) in quadrant III (spiritually poor) which was originally 7 families turned into 2 families; d) in quadrant IV (absolute poor) from 8 families to 4 families.